Cálculo da dose absorvida na cartilagem articular do joelho devido à Radiossinoviortese utilizando simulação Monte Carlo - Marzullo, Fernando Luiz (2017)
The patient-specific internal dosimetry in Radiosynoviorthese (RSV), used in this study, is based on the estimation of the energy deposited in the cartilage using Monte Carlo simulation, considering the anatomy and biodistribution of the injected Yttrium-90 Hydroxyapatite in the knee joint. For this purpose, it was necessary to develop a method based on the application of the real image of the synovial joint, including bone, articular cartilage and synovium, obtained through the 3D Magnetic Resonance Imaging (MRI) of two patients submitted to knee RSV in HUCFF / UFRJ. This research project aims to calculate the dose absorbed in the patellar, femoral and tibial cartilage by Monte Carlo with the GATE code due to knee RSV. To do this, the following tasks were performed: synovial joint modeling by segmentation of MRI images of two patients with different hemophilic arthropathy-related lesions using 3D Slicer, using the Monte Carlo method - GATE code version 7.1 - for simulation in the anatomical model constructed of the knee joint, and finally, the use of a programming routine in MATLAB environment for the elaboration of dose-volume histograms. The results obtained provided indications for a more realistic and individualized knowledge of the dose and its distribution in the cartilages of patients submitted to RSV in the knee, thus contributing to a better evaluation and understanding of what occurs with the cartilages and with the treatment itself.